2017
DOI: 10.1177/0954411917697357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of native silk fibroin powder on the physical properties and biocompatibility of biomedical polyurethane membrane

Abstract: Naturally derived fibers such as silk fibroin can potentially enhance the biocompatibility of currently used biomaterials. This study investigated the physical properties of native silk fibroin powder and its effect on the biocompatibility of biomedical polyurethane. Native silk fibroin powder with an average diameter of 3 µm was prepared on a purpose-built machine. A simple method of phase inversion was used to produce biomedical polyurethane/native silk fibroin powder hybrid membranes at different blend rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Due to the advantages of superfine technology, fibroin powder is currently being explored as a green alternative for preparing regenerated materials. Typically, fibroin powder is blended with a synthetic polymer, especially polyurethane, to meet the diversity of demand for functional materials owing to their improved mechanical properties. , Different superfine fibroin powder/polyurethane-based materials have been demonstrated in our previous studies (Figure ), i.e., breathable textile coatings, bionic fibers, efficient dye sorbents for removing dyes from textile effluents, drug delivery for controlling heparin release, and small-diameter vascular tubular materials with high biocompatibility to blood both in vivo and in vitro . However, despite the remarkable potential and diversity of fibroin powder blends, their applications have been limited by challenges including poor mechanical properties and brittleness associated with a high concentration of superfine fibroin powders. Recently, researchers have tried to improve the mechanical properties of silk fibroin blends by plasma treatment, but unfortunately, the results are not satisfactory .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of superfine technology, fibroin powder is currently being explored as a green alternative for preparing regenerated materials. Typically, fibroin powder is blended with a synthetic polymer, especially polyurethane, to meet the diversity of demand for functional materials owing to their improved mechanical properties. , Different superfine fibroin powder/polyurethane-based materials have been demonstrated in our previous studies (Figure ), i.e., breathable textile coatings, bionic fibers, efficient dye sorbents for removing dyes from textile effluents, drug delivery for controlling heparin release, and small-diameter vascular tubular materials with high biocompatibility to blood both in vivo and in vitro . However, despite the remarkable potential and diversity of fibroin powder blends, their applications have been limited by challenges including poor mechanical properties and brittleness associated with a high concentration of superfine fibroin powders. Recently, researchers have tried to improve the mechanical properties of silk fibroin blends by plasma treatment, but unfortunately, the results are not satisfactory .…”
Section: Introductionmentioning
confidence: 99%
“…It has been verified that TSF has good biocompatibility, permeability and biodegradability, with a low inflammatory response and other favorable qualities (28,29). TSF supports cell growth, proliferation and differentiation; in vivo studies have also reported that it facilitates tissue repair (30,31).…”
Section: Discussionmentioning
confidence: 95%
“…Polylactic acid resin (6202D) with an average molecular weight of 97 kDa consisting of 98% l ‐lactide and 2% d ‐lactide units was purchased from Nature Works LLC, USA. Silk fibroin protein was obtained from silk and made in laboratory, and the silk fibroin used in this experiment is water‐insoluble 24–25 . The 1,4‐dioxane was purchased from Sinopharm Chemical Reagent Co., Ltd. Tetracycline hydrochloride (C 22 H 24 N 2 O 8 .…”
Section: Methodsmentioning
confidence: 99%